ANALISIS SISTEM MANAJEMEN PROGRAM P2 ISPA DI PUSKESMAS PEGANDAN KOTA - Rizki Tri Putriarti; Anneke Suparwati; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Pneumonia becomes the biggest concern in public health among any other respiratory diasease (ISPA) because pneumonia can cause death especially in children under five. Evaluation of P2 ISPA program at Puskesmas is measured by calculating the coverage of pneumonia case finding in children under five. Puskesmas that has the lowest coverage in Semarang is Puskesmas Pegandan (1.07%), while DKK’s target is 39%. Problem faced by Puskesmas Pegandan are there’s no specific fund allocated for the program, and there’re no KIE tools for the program. The purpose of this research is to analyze the management system of P2 ISPA program at Puskesmas Pegandan.The method used is qualitative method, with 2 main and 4 triangulation informants. The result showed that commitment of the implementer and DKK in this program are lacking. This can be seen that there’s no training for Puskesmas due to the limited fund for this program in DKK, there’re no specific fund allocated for the program because there’s no detailed program’s planning. There’re no KIE tools for the program, but Puskesmas not trying asked for that to DKK, and the manual of the program hasn’t been fully understood by Puskesmas. The program’s planning not made in detail because P2 ISPA isn’t a priority program, and this program rarely discussed in both supervision or mini lokakarya. No specific teams for the program. This program’s output is very low because Puskesmas never diseminate information to the public so they can’‘t really understand about this diasease. There has been no follow-up given by Puskesmas head and DKK. It’s necessary to do intervention to the implementers and stakeholders to be more committed for this program, so that this program can run optimally.